Reviews. Issue 1 (1st December 2012) - Allen, Fiona; Fallon, Benjamin; Hutchinson, Mark; Coombs, Gretchen
'Art Turning Left: How Values Changed Making 1789–2013', Tate Liverpool, Liverpool, United Kingdom, 8 November 2013–2 February 2014Anne Ben BarbarMiyim?/Mom, am I Barbarian?, Istanbul Biennial 2013 Istanbul, Turkey, 25 June–25 September 2013Tarrying with the Avant-GardeBrave New Avant Garde: Essays on Contemporary Art and Politics, Marc Léger (2012) Winchester: Zero Books, 198 pp., ISBN: 9781780990507, p/bk, £12.99Artificial Hells: Participatory Art and the Politics of Spectatorship, Claire Bishop (2012) London: Verso, 382 pp., ISBN: 9781844676903, p/bk